Pathways Out of Poverty During an Economic Crisis : An Empirical Assessment of Rural Indonesia - McCulloch, Neil; Weisbrod, Julian; Timmer, C. Peter (World Bank, Washington, DC, 2012)
Most poor people in developing countries still live in rural areas and are primarily engaged in low productivity farming activities. Thus pathways out of poverty are likely to be strongly connected to productivity increases in the rural economy, whether they are realized in farming, in rural nonfarm enterprises, or by way of rural-urban migration. The authors use cross-sectional data from the Central Statistical Board for 1993 and 2002, as well as a panel data set from the Indonesia Family Life Survey for 1993 and 2000, to show which pathways out of poverty were most successful over this period. The findings suggest that increased engagement of farmers in rural nonfarm enterprises is an important route out of rural poverty, but that most of the rural agricultural poor that exit poverty still do so while remaining rural and agricultural. So changes in agricultural prices, wages, and productivity still play a critical role in moving people out of poverty.